(untitled) (Global Journal of Human-Social Science, 2024)
Child protection is an issue in Indonesia which has a varied cultural heritage and has experienced economic downturns According to Arliman 2017 Indonesia has created policies efforts and governmental and non-governmental organizations to ensure Children s protection and wellness The nation s legal structure consists of global and across-the-country conventions which disclose the relevance of the initiatives placed by the federal government to protect and safeguard Children s lawful rights According to Vaitla et al 2017 the focus has been on securing wellness and constitutional freedoms specifically in the problem of early marriages The country s decision to promote child protection through fundamental laws such as the constitution originates from the implications for the future and children s health Olojede et al 2020 reveal numerous problems in managing children s issues such as forced marriage denying their basic civil liberties and gender-based violence Despite the federal government s efforts numerous difficulties proceed and remain prevalent in different Indonesian areas and regions